Human immuno-therapeutics for cancer treatment of dogs? - Klingemann, Hans (Frontiers in Veterinary Science, 2025)
Immunotherapy for humans has enjoyed a recent boost of treatment options that, however, has not translated into the veterinary field. Developments like monoclonal antibodies against immune checkpoint inhibitors and tumor-specific CAR-T cells have broadened treatment options for human cancer patients but the canine space has not benefited from those advancements. These novel treatments are expensive to develop for the canine market and are not necessarily promising a significant financial return for the pharmaceutical industry. Hence the question is whether there are immunotherapies that work for humans and that also have some cross-species (xenogeneic) activity in dogs, but at the same time have only minimal side effects and are affordably priced. Can such an approach be considered at all assuming that the disparity could result in an immediate rejection of the administered ‘product’ with all the potential side effects? Maybe this assumption is not necessarily founded on solid data and this brief review attempts to summarize of what is actually known on the treatment of canine cancers with human immuno-therapeutics.